Harry the dirty dog - Zion, Gene.; Graham, Margaret Bloy ([New York] : HarperCollins, 2006)
When a white dog with black spots runs away from home, he gets so dirty his family doesn't recognize him as a black dog with white spots.
Child Study Children's Book Committee
Elem. School Library Collection
Wilson's Children
Child Study Children's Book Committee, September 2007
Elem. School Library Collection, March 1998
Horn Book, February 2012
Keywords: Cleanliness -- Fiction; Dogs -- Fiction; Cleanliness -- Fiction; Dogs -- Fiction